On the other side of shame : a non-fiction account - Jowell, Joanne (Department of English Language and Literature, 2014)
Lynette Langman's telephone rang on a Sunday night in 2001, heralding the call that would unravel her life. For forty long years, she had waited to hear news about the son she gave up for adoption when she was virtually a child herself. His birth had remained a closely guarded secret, hidden even from those who knew her best. And now his disclosure would unleash years of bottled questions and confessions.